Hot deformation behavior of micro-alloyed steel using processing maps developed with different constitutive equations - Thakur, Suman; Das, Alok Kumar; jha, Bimal Kumar (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
The hot workability of microalloyed steel was studied in the deformation temperature range of 850-1200oC and strain rate of 0.001-100s-1. The constitutive relation of flow stress with temperature, strain rate and strain was established to construct processing maps of the microalloyed steel. The processing maps were constructed using conventional power law, integral method and Arrhenius equations. The developed processing maps were used to predict the optimal hot deformation conditions and validated with metallurgical examinations. The safe regime for hot working of the experimental steel was found to be in the intermediate temperature-strain rate range (1000-1150oC- 0.001-10 s-1), where the deformation process is dominated by dynamic recrystallization and dynamic recovery of the austenitic phase. The processing map constructed using Arrhenius equations increases continuously with increase in deformation temperature and decrease in strain rate and does not reveal relevant information of hot workability with respect to deformation temperature and strain rate.
Keywords: Deformation, Processing map, Microalloyed, Arrhenius Equation